The Fight Against Child Trafficking Breaking the Cycle of Structural Violence - Narminio, Elisa (Taylor & Francis, 2023)
child trafficking; human trafficking; trafficking; anti-trafficking policies; EU-ASEAN; ASEAN; Human Rights; governance